The thermodynamics of deformed metamorphic rocks: A review - Hobbs, Bruce E.; Ord, Alison; Regenauer-Lieb, Klaus (Journal of structural geology, 2011)
The deformation of rocks is a disequilibrium and strongly non-linear phenomenon with a number of interacting chemical, thermal and microstructural processes operating simultaneously. We review progress in this area over the past 30 years. Deforming-chemically reacting systems are dissipative systems and hence are characterised by highly ordered structures that develop through cooperative processes once parameters such as critical strains, strain-rates, fluid infiltration rates, damage densities or temperatures are attained. Such criticality is the hallmark of deformed rocks at all length scales and is the basis for a diverse range of structures such as foliations and lineations produced by metamorphic differentiation, rotation recrystallisation, folding, boudinage and micro to regional scale fracture systems. Criticality is identified with classical criticality and not self-organised criticality. The first and second laws of thermodynamics are used to show that such structural diversity arises from reaction-diffusion-deformation equations. Criticality of the system is associated with the stored energy becoming non-convex and structures arise in order to minimise this non-convex energy. These structures are scale invariant and hence are characterised by fractal and minimal surface geometries. Thermodynamics is a powerful discipline to integrate seemingly unrelated processes in structural geology and produce an integrated approach to the subject that crosses all length scales. ► Generalised Thermodynamics unifies processes operating during deformation and metamorphism. ► The unifying principle is: dissipative processes are coupled by the second law of thermodynamics. ► Deformation-metamorphic processes are described by reaction diffusion deformation equations. ► Structures form to minimise the (non-convex) Helmholtz energy and are critical phenomena. ► Localised folds are the norm in deformed rocks and also form to minimise the Helmholtz energy.